PRIMARY SCHOOL TEACHER’ PERCEPTIONS TOWARD ONLINE LEARNING DURING PANDEMIC COVID-19 - Roslaini; Lailis Soraya (UICELL, 2021)
Since the outbreak of Covid-19, the government issued the policy of study from home (SFH) by which it revealed pros and cons from society. From the website of gtk.kemdikbud.go.id, it was stated that starting offline learning is still being discussed because the covid-19 pandemic is not over. This situation really annoyed the primary school teachers for their teaching learning process. Concerning with this unclear decision, it is necessary to explore the teachers’ perceptions towards the learning process that has been done since it may be used as a consideration for the government to prolong the study from home. To get the data of this study, open and close-ended questionnaires were used for 30 respondents who were domiciled in Jakarta, Bogor, Tangerang, and Bekasi. They are all primary school teachers who are teaching English. Afterwards, the results of the survey were analyzed using a quantitative and qualitative method in finding the teachers’ perceptions towards online learning, Finally, the results showed that there are two categories of teachers’ perception, i.e., negative perceptions and positive perceptions. The negative perceptions of the teachers are related to the internet connection, uncooperative students’ parents, lack of facilities, students’ laziness, and students’ understanding of materials; whereas the positive perceptions of the teachers are the increase of teachers’ knowledge of technology, flexible time in teaching, capable of using variety of teaching applications. Keywords: Teachers’ Perceptions, Online Learning, Covid-19, SFH